Base‐Free Oxidation of Glycerol Using Titania‐Supported Trimetallic Au–Pd–Pt Nanoparticles. Issue 5 (25th November 2013) - Kondrat, Simon A.; Miedziak, Peter J.; Douthwaite, Mark; Brett, Gemma L.; Davies, Thomas E.; Morgan, David J.; Edwards, Jennifer K.; Knight, David W.; Kiely, Christopher J.; Taylor, Stuart H.; Hutchings, Graham J.
Abstract Base‐free selective oxidation of glycerol has been investigated using trimetallic Au–Pd–Pt nanoparticles supported on titania and their corresponding bimetallic catalysts. Catalysts were prepared by the sol‐immobilization method and characterized by means of TEM, UV/Vis spectroscopy, diffuse reflectance infrared fourier transform spectroscopy, X‐ray photoelectron spectroscopy, and microwave plasma–atomic emission spectroscopy. It was found that of the bimetallic catalysts, Pd–Pt/TiO2 was the most active with high selectivity to C3 products. The addition of Au to this catalyst to form the trimetallic Au–Pd–Pt/TiO2, resulted in an increase in activity relative to Pd–Pt/TiO2. The turnover frequency increased from 210 h−1 with the Pd–Pt/TiO2 catalyst to378 h−1 for the trimetallic Au–Pd–Pt/TiO2 catalyst with retention of selectivity towards C3 products.